Ex-post effects of trade liberalization in the Philippines - Ramon L. Clarete (University of the Philippines, School of Economics (UPSE), 2005)
This paper examines the Philippine experience with trade liberalization policies and their impact on the economy. Although the relationship between trade liberalization and poverty is not straightforward, empirical evidence suggests that there are benefic
Keywords: 330